2021
DOI: 10.1021/acsnano.0c09404
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Mediated Spin–Orbit Torque Enhancement in Pt/Co on Flexible Substrate

Abstract: Current-induced magnetization switching by spin–orbit torque generated in heavy metals offers an enticing realm for energy-efficient memory and logic devices. The spin Hall efficiency is a key parameter in describing the generation of spin current. Recent findings have reported enhancement of spin Hall efficiency by mechanical strain, but its origin remains elusive. Here, we demonstrate a 45% increase in spin Hall efficiency in the platinum/cobalt (Pt/Co) bilayer, of which 78% of the enhancement was preserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…This result led to the conclusion that SOT modulation is attributed to the extrinsic part. A similar effect was previously reported in a comparable material combination (double-layer Co/Pt) with an increase of 28.5% in a Co/Pt system on a Kapton film 62 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This result led to the conclusion that SOT modulation is attributed to the extrinsic part. A similar effect was previously reported in a comparable material combination (double-layer Co/Pt) with an increase of 28.5% in a Co/Pt system on a Kapton film 62 .…”
Section: Resultssupporting
confidence: 87%
“…As the applied strain is increased, the racetrack stripe gets narrower, consequently resulting in an increase in the metal’s resistivity. According to the discussion 62 , the heightened efficiency of SOT efficiency under elongation strain is attributed to extrinsic scattering. It was reported that in heavy metals, like Pt, Ta, W, Pd the intrinsic scattering typically dominates over the extrinsic.…”
Section: Resultsmentioning
confidence: 97%
“…This effect can be considered an evolution of the SHE in electronic systems, which has a wide range of applications in precision metrology, quantum imaging, and micro-imaging [8]. In the FM/HM heterostructure, SOT originates from the bulk SHE and/or the interface Rashba-Edstein effect [9][10][11][12][13]. For SHE, the charge current flowing through the HM can be converted into a spin current due to the strong spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…For SHE, the charge current flowing through the HM can be converted into a spin current due to the strong spin-orbit coupling (SOC). The spin current is injected from the HM to the FM layer, and a torque is applied to the FM layer, which can switch the magnetization [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…Logic-in-memory architectures provide a possible solution for future data storage and processing. Especially, spin logic devices based on spin–orbit torque (SOT) induced magnetization switching show particular advantages in constructing logic-in-memory architectures with high computing capability, low power dissipation, and good programming capability. , In 2020, Lim et al developed a reconfigurable SOT-driven logic device using a double Hall cross structure with an integrated bias field line for the generation of a local bias field . In 2022, Fan et al realized four different magnetic configurations in IrMn/Co/Ru/CoPt/CoO multilayers, which are programmable by magnetic field and current .…”
mentioning
confidence: 99%